PANDEMIC-INDUCED STRESS ESCALATION AMONG WOMEN IN NORTH MACEDONIA - Ilieva, Natasha; Poposka, Verica; Iliev, Darko; Aleksioska Papestiev, Irena; Daneva Markova, Ana; Tofoski, Gligor; Jovanovska, Viktorija; OrovÄanec, Nikola (Journal of Morphological Sciences; Vol 6 No 2 (2023): JMS, 2023)
The COVID-19 pandemic, officially declared by the World Health Organization on 11/03/2020, when the SARS-CoV-2 virus had spread to 114 countries with >118,000 cases, prompted significant changes in daily life and potentially increased stress levels. This study aimed to investigate the difference in stress levels among women in North Macedonia, both before and during the COVID-19 pandemic. A cross-sectional study was conducted using a questionnaire, which incorporated the Perceived Stress Scale (PSS) to assess stress levels pre- and mid-pandemic. More than 500 women aged 18 to 45, who sought examinations at the University Gynaecology and Obstetrics Clinic from March 2022 to March 2023, were invited to participate; 206 women accepted the invitation. The findings indicated that the participants' stress level scores were significantly higher post-March 2020 compared to pre-March 2020 (Z = 8.13, p < 0.001). These results suggest that the COVID-19 pandemic has substantially affected the stress levels experienced by women in North Macedonia. This is aligned with previous studies indicating increased stress levels during the pandemic, primarily attributed to health concerns, financial difficulties, and social isolation. This study provides substantial evidence of the significant impact of the COVID-19 pandemic on women's stress levels in North Macedonia. Future research should focus on identifying factors contributing to heightened stress levels among women during the pandemic. This will help formulate effective interventions to counteract the negative impact of the pandemic on this population's mental health. Key words: stress, women, COVID-19, pandemics, Perceived Stress Scale (PSS).